Synthesis of new hydantoin-3-ethanethiol derivatives - Oh, C.-H.; Lee, K.-S.; Roh, E.-J.; Kwon, S.-K.; Cho, J.-H. (1994)
5-sec-Butylthiomethyl-5-alkyl (methyl or phenyl) hydantoins (3？x) were prepared by the reaction of sec-butylthiomethyl alkyl (methyl or phenyl) ketone (1？2), potassium cyanide and ammonium carbonate. 3-(2-Bromoethyl) hydantoins (5？6) were the reaction products of 5-sec-butylthiomethyl-5-alkyl (methyl or phenyl) hydantoin and 1,2-dibromoethane in the presence of potassium hydroxide. Alkylation of 5 and 6 with an excess of alkyl (methyl or ethyl) iodide in THF with sodium hydride as base gave three 1-alkyl (methyl or ethyl)-3-(2-bromoethyl) hydantoins (7？9). Treatment of the 2-bromoethyl group with potassium thioacetate and triethylamine gave three 1-alkyl (methyl or ethyl)-3-(2-acetylthioethyl) hydantoins (10？12). Hydrolysis of the 2-acetylthioethyl group with sodium hydroxide in methanol afforded the three 1-alkyl (methyl or ethyl)-3-(2-mercaptoethyl) hydantoins. ？ 1994, The Pharmaceutical Society of Korea. All rights reserved.
Keywords: hydantoin derivative; article; drug synthesis